Representations on social participation in the education in school councils in the north of México (Foro de Educacion, 2016)
This work had as objectives to know the way in which basic education school councils understand and implement the policy of social participation, as well as analyze the senses and representations that it has on the educational community. Through the  study in specific cases, we chose three municipal councils and six school. We conducted interviews with members of the educational community, and since social representations (SR), have used two basic instruments: the elaboration of phrases and words free association. The results show us, on the one hand, the great weight that has representation of the councils at various levels under the figure of the formality of procedures, simple procedures that do not seem to have substantive impact and material in social participation. And on the other hand, a misunderstanding or distance between the SR of participation and education.